Wasabia japonica is a potential functional food to prevent colitis via inhibiting the NF-κB signaling pathway. Issue 8 (20th July 2017) - Kang, Ju-Hee; Choi, Seungho; Jang, Jeong-Eun; Ramalingam, Prakash; Ko, Young Tag; Kim, Sun Yeou; Oh, Seung Hyun
Abstract : Wasabia Japonica ameliorates DSS-induced colitis in animal model by inhibiting pro-inflammatory signaling. Abstract : Inflammatory bowel diseases (IBDs), including Crohn's disease (CD) and ulcerative colitis (UC), are prevalent and debilitating health problems worldwide. Many types of drugs are used to treat IBDs, but they exhibit adverse effects such as vomiting, nausea, abdominal pain, diarrhea, etc . In order to overcome the limitations of current therapeutic drugs, scientists have searched for functional foods from natural resources. In this study, we investigated the anti-colitic effects of Wasabia japonica extract in a DSS-induced colitis model. Wasabi japonica is a plant of the Brassicaceae family that has recently been reported to exhibit properties of detoxification, anti-inflammation, and induction of apoptosis in cancer cells. In this study, we generated wasabi ethanol extract (WK) and assessed its anti-colitic effect. In addition, in order to improve delivery of the extract to the colon, WK was coated with 5% Eudragit S100 (WKE), after which the anti-colitic effects of WKE were assessed. In conclusion, WK prevented development of colitis through inhibition of the NF-kB signaling pathway and recovery of epithelial tight junctions. In addition, the anti-colitic effect of WK was enhanced by improving its delivery to the colon by coating the WK with Eudragit S100. Therefore, we suggest that wasabi can be used as a new functional food to prevent IBDs due to its anti-colitic effect.